THE IMPLEMENTATION OF DISCOVERY LEARNING MODEL IN TEACHING ASKING AND GIVING OPINION - Nur, Amani Rohadatul Aisy (Bulletin of Scientific Reseach in English Education, 2024)
The purpose of this research was to explore deeper insights and knowledge about the implementation of the discovery learning model and to investigate the challenges of English teacher when implementing the discovery learning model in teaching asking and giving opinion. This research employed a case study under a qualitative approach. This research was conducted with eleventh grade Science 7 Senior State 1 Ciamis. Meanwhile, the subject of this study was an English teacher. This data were collected through pre-interview, post-interview, observation, and document analysis. The results of the research showed that the teacher does not apply all of the discovery learning syntax at both meetings. Meanwhile, the teacher still faces challenge in implementing this learning model in their class because there are some students who are passive during the learning process. In conclusion, even though at the second meeting the syntax was not carried out properly and the students’ character was constrained, the learning objectives could be achieved and the teacher was able to effectively manage these problems.